Reducing Electric Power Losses in the System of Power Supply Due to Compensation of Higher Harmonics of Currents: Economic and Energy Efficiency Outcomes - Averbukh, Mikhail A.; Zhukov, Nikolay A.; Khvorostenko, Stanislav V.; Panteleev, Vasiliy I. (International Journal of Energy Economics and Policy, 2019)
The issue of increasing energy efficiency and energy saving is of great importance for the countries with high energy intensity of the gross domestic product, including Russia and the rest of the Commonwealth of Independent States. The measures adopted in Russia on the federal and regional level as part of the State Program on Energy Efficiency and Energy Development are focused on reducing the energy intensity of Russia’s gross domestic product and introduce sustainable practices on energy saving in Russia’s commercial and budget sectors. This paper presents a case study describing the way to reduce electric power losses in a system of power supply (SPS) of an industrial enterprise. In particular, the case study determines the level of the higher harmonic components of current and voltage at the existing enterprise for the production of reinforced concrete products. The results of the experiment were reproduced using a simulation model of the power supply system in the Matlab/Simulink package. A comparative analysis of using a passive and hybrid filter compensating device to reduce the level of the higher harmonics of current and voltage was carried out by means of modeling. The active losses in the SPS from non-sinusoidal mode are calculated. In addition, the economic effect of using the proposed method is estimated. Keywords: Energy Efficiency, Industry, Electric Power Losses, Higher Harmonics of Currents JEL Classifications: Q29, Q49, L94 DOI: https://doi.org/10.32479/ijeep.7693